Implementasi Algoritma Mars Pada Pengamanan SMS - Nurainun Hasanah Sinaga; Muhammad Syahrizal (STMIK Budi Darma, 2020)
SMS (Short Message Service) is a popular communication technology revolution. The development of computerized technology has been very advanced. SMS is very vulnerable to data theft or theft by irresponsible parties. For the sake of maintaining the security of SMS can be done by using cryptographic techniques. Cryptographic techniques can encode text messages by encrypting them into passwords that are not understood. Mars algorithm is an algorithm that uses a 128-bit key and the encryption process consists of 32 rounds. This symmetry algorithm will produce a higher level of security for the ultrasound image because it can encode it into a form of cipher with a process that is complex enough so that it will be difficult for cryptanalysts to access the image. This research will use the Mars algorithm for the encryption and decryption process, so the process needs to go through several long stages in order to produce the final cipher. This study describes the process of securing SMS by encoding it based on the Mars algorithm, in the form of a password that is difficult for others to understand and understand. This is done as an effort to minimize acts of misuse of SMS